Insights into the mineralogy and distribution of Co, Ni, As and Bi in the sediment-hosted polymetallic ores of the Kupferschiefer in Lusatia, Germany - Zahra Nourizenouz; Max Frenzel; Bradley Martin Guy; Aratz Beranoaguirre; Jens Gutzmer (Journal of Geochemical Exploration, 2026)

Trace elements distribution in colloform chalcopyrite and tennantite: insights from Butte (USA) and Lisheen (Ireland) - Alexandre Cugerone; Denis Fougerouse; Max Frenzel; Kalin Kouzmanov; William D.A. Rickard; Kai Luo; Vincent Motto-Ros; Valby van Schijndel; Lorenzo Tavazzani; David W. Saxey; Steven M. Reddy (Geochimica et Cosmochimica Acta, 2026)

The deportment of silver in Kupferschiefer ores at the Spremberg-Graustein-Schleife deposit, Germany - Zahra Nourizenouz; Bradley Martin Guy; Jens Gutzmer; Doreen Ebert; Ralph Braumann; Max Frenzel (Mineralium Deposita, 2026)
The high-grade stratabound copper ores of the Central European Kupferschiefer are one of the world’s most important sources of silver. Despite its economic significance, the mineralogical partitioning of silver within the Kupferschiefer ores is generally not well understood, other than the fact that silver minerals are not sufficiently abundant to account for the bulk of the silver content. This study provides the first fully quantitative silver deportment for Kupferschiefer-type ores, using the Spremberg-Graustein-Schleife project in Germany as a case study. Our comprehensive analytical approach integrates scanning electron microscope (SEM)-based automated mineralogy and electron probe micro-analysis (EPMA) on exploration drill-core samples collected from different host rocks and different metal tenor. The results were validated using bulk geochemical data, and uncertainties were assessed with Monte Carlo simulations. The results demonstrate that the majority of the silver within high-grade Cu-rich ores occurs as a trace constituent in the ore-forming Cu(-Fe) sulfides (chalcocite group minerals, covellite, bornite, and chalcopyrite). In samples containing little copper, however, Fe sulfides host the majority of the silver in the form of micro-inclusions within copper-enriched crystal growth zones and substitution within the crystal lattice. The close association of copper and silver has important implications for ore genesis and mineral processing. These implications may well transfer to other by-products and other examples of polymetallic sediment-hosted copper mineral systems.

Behaviour of the critical elements As, Bi, In, Sb, and Te during processing of a skarn ore: A case study of the Ruwai Zn-Pb-Ag Deposit, Central Kalimantan, Indonesia - Shelly M. Faizy; Doreen Ebert; Alkis Kontonikas-Charos; Mathias Burisch; Arifudin Idrus; Ernowo Ernowo; Anggara Widyastanto; Max Frenzel (Minerals Engineering, 2025)

Optimizing an expensive multi-objective building performance problem: Benchmarking model-based optimization algorithms against metaheuristics with and without surrogates - Max Zorn; Luisa Claus; Christian Frenzel; Thomas Wortmann (Energy and Buildings, 2025)

Molybdenite Re-Os geochronology and conditions of formation of potassic and sodic-calcic alteration associated with the Plaka porphyry Mo-Cu system, Lavrion, Greece - Panagiotis Voudouris; Vasilios Melfos; Margarita Melfou; Alexandre Tarantola; Max Frenzel; Paul G. Spry; Konstantinos Soukis; Christophe Scheffer; Olivier Vanderhaeghe; Laurie Reisberg; Lambrini Papadopoulou; Christina Stouraiti; et al. (Journal of Geochemical Exploration, 2025)

Mineralogy, mineral chemistry, and genesis of Cu-Ni-As-rich ores at Lisheen, Ireland - Max Frenzel; Markus Röhner; Nigel J. Cook; Sarah Gilbert; Cristiana L. Ciobanu; John F. Güven (Mineralium Deposita, 2025)
The Irish Orefield is characterised by the presence of both Zn-Pb- and Cu-Ni-As-rich deposits, prospects, and orebodies in similar structural and stratigraphic positions. However, the genetic relationships between these mineralisation types are still debated. In this article, we present new mineralogical, paragenetic, and mineral-chemical observations from the Cu-Ni-As-rich ores at the classic Lisheen deposit, County Tipperary. These observations indicate the intimate association and cogenetic nature of these ores with the more abundant Zn-Pb-rich mineralisation. Specifically, both mineralisation types appear to have formed at the same time, under similar physicochemical conditions, and from the same ore fluids. In addition, both types of mineralisation contain elevated Ge contents. The cogenetic nature of the two mineralisation types, the relative absence of Cu-Ni-As-rich ores from most of the larger Irish-type Zn-Pb deposits compared to expectations derived from probable ore fluid compositions, and finally, the known geological characteristics of larger Cu-Ni-As-rich ore bodies, like Gortdrum, indicate that significant Cu-Ni-As-rich mineralisation could be present at lower stratigraphic levels across the Irish Orefield. Areas with extensive known Zn-Pb mineralisation are expected to be particularly prospective for such ores, which may occur at stratigraphic levels as deep as the Old Red Sandstone. This may have additional implications beyond Ireland, and could point to the potential for undiscovered Cu-rich ores in low-temperature carbonate-hosted Zn-Pb districts elsewhere.

From exploration to production: Understanding the development dynamics of lithium mining projects - Laura Buarque Andrade; Max Frenzel; Britta Bookhagen; Carolin Kresse; Michael Schmidt; Nedal Nassar; Elisa Alonso; Ensieh Shojaeddini; Dirk Sandmann (Resources Policy, 2024)

A study on the desulfurization of sulfidic mine tailings for the production of a sulfur-poor residue - Ana Luiza Coelho Braga de Carvalho; Victor Albuquerque de Carvalho; Rosie Blannin; Alexandra Gomez Escobar; Max Frenzel; Martin Rudolph; André Carlos Silva; Daniel Goldmann (Minerals Engineering, 2023)

Timing of magmatic-hydrothermal activity in the Variscan Orogenic Belt: LA-ICP-MS U–Pb geochronology of skarn-related garnet from the Schwarzenberg District, Erzgebirge - Nils Reinhardt; Axel Gerdes; Aratz Beranoaguirre; Max Frenzel; Lawrence D. Meinert; Jens Gutzmer; Mathias Burisch (Mineralium Deposita, 2022)
Here, we present in situ U–Pb laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) ages of andradite-grossular garnet from four magmatic-hydrothermal polymetallic skarn prospects in the Schwarzenberg District, Erzgebirge (Germany), located in the internal zone of the Variscan Orogenic Belt. Within the geochronological framework of igneous rocks and hydrothermal mineralization in the Erzgebirge, the obtained garnet ages define three distinct episodes of Variscan skarn formation: (I) early late-collisional mineralization (338–331 Ma) recording the onset of magmatic-hydrothermal fluid flow shortly after the peak metamorphic event, (II) late-collisional mineralization (~ 327–310 Ma) related to the emplacement of large peraluminous granites following large-scale extension caused by orogenic collapse and (III) post-collisional mineralization (~ 310–295 Ma) contemporaneous with widespread volcanism associated with Permian crustal reorganization. Our results demonstrate that the formation of skarns in the Schwarzenberg District occurred episodically in all sub-stages of the Variscan orogenic cycle over a time range of at least 40 Ma. This observation is consistent with the age range of available geochronological data related to magmatic-hydrothermal ore deposits from other internal zones of the Variscan Orogenic Belt in central and western Europe. In analogy to the time–space relationship of major porphyry-Cu belts in South America, the congruent magmatic-hydrothermal evolution in the internal zones and the distinctly later (by ~ 30 Ma) occurrence of magmatic-hydrothermal ore deposits in the external zones of the Variscan Orogenic Belt may be interpreted as a function of their tectonic position relative to the Variscan collisional front.

Evolution of a hydrothermal ore-forming system recorded by sulfide mineral chemistry: a case study from the Plaka Pb–Zn–Ag Deposit, Lavrion, Greece - Max Frenzel; Panagiotis Voudouris; Nigel J. Cook; Cristiana L. Ciobanu; Sarah Gilbert; Benjamin P. Wade (Mineralium Deposita, 2022)
Laser ablation-inductively coupled plasma-mass spectrometry and electron-probe microanalysis were used to investigate the trace-element contents of sphalerite, chalcopyrite and pyrite from the Plaka Pb–Zn–Ag deposit. Using petrographic observations, the analytical results could be linked to the temporal evolution of the Plaka ore-forming system. Sphalerite chemistry reliably records the temperature and f S 2 evolution of the system, with estimated formation temperatures reproducing the microthermometric results from previous fluid-inclusion studies. Chalcopyrite chemistry also shows systematic variations over time, particularly for Cd, Co, Ge, In, Sn and Zn concentrations. Measurable pyrite was only found in association with early high-temperature mineralisation, and no clear trends could therefore be identified. We note, however, that As and Se contents in pyrite are consistent with formation temperatures estimated from co-existing sphalerite. Statistical analysis of the sphalerite data allowed us to identify the dominant geological controls on its trace-element content. The three investigated factors temperature, f S 2 , and sample location account for > 80% of the observed variance in Mn, Fe, Co, Ga, Ge, In, Sb and Hg concentrations, and > 60% of the observed variance in Cd and Sn concentrations. Only for Cu and Ag concentrations is the explained variance < 50%. A similarly detailed analysis was not possible for chalcopyrite and pyrite. Nevertheless, comparison of the results for all three investigated minerals indicates that there are some systematic variations across the deposit which may be explained by local differences in fluid composition.

Insights into Holocene relative sea‐level changes in the southern North Sea using an improved microfauna‐based transfer function - Juliane Scheder; Friederike Bungenstock; Kristin Haynert; Anna Pint; Frank Schlütz; Peter Frenzel; Achim Wehrmann; Helmut Brückner; Max Engel (Journal of Quaternary Science, 2022)
In light of global warming and rising relative sea level (RSL), detailed reconstructions of RSL histories and their controlling processes are essential in order to manage coastal‐protection challenges. This study contributes to unravelling Holocene RSL change on the East Frisian North Sea coast in high resolution and with a new approach for the German Bight. For the first time, a transfer function (vertical error: 29.7 cm ≙ ~11% of the mean tidal range) for RSL change based on a combined training set of benthic foraminifers and ostracods from the back‐barrier tidal basin of Spiekeroog is applied to the Holocene record of the back‐barrier tidal basin of Norderney. The resulting RSL curve for the Norderney tidal basin is corrected for decompaction and shows a deceleration in RSL rise between 6000 and 5000 cal bp. The smallest possible error envelope (~1 m) results from the good suitability of salt‐marsh layers between 5000 and 4000 cal bp. The RSL curve provides an approach towards the closure of the common data gap of peat‐based curves for the southern North Sea related to a lack of basal peats in the youngest age range, and verifies regional differences in glacial isostatic adjustment.

Li-Co–Ni-Mn-(REE) veins of the Western Erzgebirge, Germany—a potential source of battery raw materials - Mathias Burisch; Max Frenzel; Henning Seibel; Albert Gruber; Marcus Oelze; Jörg A. Pfänder; Cynthia Sanchez-Garrido; Jens Gutzmer (Mineralium Deposita, 2021)
Situated in the western Erzgebirge metallogenetic province (Vogtland, Germany), the Eichigt prospect is associated with several quartz-Mn-Fe-oxyhydroxide veins that are exposed at surface. Bulk-rock geochemical assays of vein material yield high concentrations of Li (0.6–4.1 kg/t), Co (0.6–14.7 kg/t), and Ni (0.2–2.8 kg/t), as well as significant quantities of Mn, Cu, and light rare earth elements, a very unusual metal tenor closely resembling the mixture of raw materials needed for Li-ion battery production. This study reports on the results of a first detailed investigation of this rather unique polymetallic mineralization style, including detailed petrographic and mineralogical studies complemented by bulk rock geochemistry, electron microprobe analyses, and laser ablation inductively coupled mass spectrometry. The mineralized material comprises an oxide assemblage of goethite hematite, hollandite, and lithiophorite that together cement angular fragments of vein quartz. Lithiophorite is the predominant host of Li (3.6–11.1 kg/t), Co (2.5–54.5 kg/t), and Ni (0.2–8.9 kg/t); Cu is contained in similar amounts in hollandite and lithiophorite whereas light rare earth elements (LREE) are mainly hosted in microcrystalline rhabdophane and florencite, which are finely intergrown with the Mn-Fe-oxyhydroxides. 40 Ar/ 39 Ar ages (~ 40–34 Ma) of coronadite group minerals coincide with tectonic activity related to the Cenozoic Eger Graben rifting. A low-temperature hydrothermal overprint of pre-existing base metal sulfide-quartz mineralization on fault structures that were reactivated during continental rifting is proposed as the most likely origin of the polymetallic oxyhydroxide mineralization at Eichigt. However, tectonically enhanced deep-reaching fracture-controlled supergene weathering cannot be completely ruled out as the origin of the mineralization.

Laser ablation ICP-MS trace element systematics of hydrothermal pyrite in gold deposits of the Kalgoorlie district, Western Australia - Marcelo Godefroy-Rodríguez; Steffen Hagemann; Max Frenzel; Noreen J. Evans (Mineralium Deposita, 2020)

The geometallurgical assessment of by-products—geochemical proxies for the complex mineralogical deportment of indium at Neves-Corvo, Portugal - Max Frenzel; Kai Bachmann; João R. S. Carvalho; Jorge M. R. S. Relvas; Nelson Pacheco; Jens Gutzmer (Mineralium Deposita, 2019)

Trace element geochemistry of sphalerite in contrasting hydrothermal fluid systems of the Freiberg district, Germany: insights from LA-ICP-MS analysis, near-infrared light microthermometry of sphalerite-hosted fluid inclusions, and sulfur isotope geochemistry - Matthias E. Bauer; Mathias Burisch; Jörg Ostendorf; Joachim Krause; Max Frenzel; Thomas Seifert; Jens Gutzmer (Mineralium Deposita, 2019)

Discrimination and Variance Structure of Trace Element Signatures in Fe-Oxides: A Case Study of BIF-Mineralisation from the Middleback Ranges, South Australia - Marija Dmitrijeva; Andrew V. Metcalfe; Cristiana L. Ciobanu; Nigel J. Cook; Max Frenzel; William M. Keyser; Geoff Johnson; Kathy Ehrig (Mathematical Geosciences, 2018)

Erratum to: On the geological availability of germanium - Max Frenzel; Marina P. Ketris; Jens Gutzmer (Mineralium Deposita, 2014)

On the geological availability of germanium - Max Frenzel; Marina P. Ketris; Jens Gutzmer (Mineralium Deposita, 2014)

A prehistoric tsunami induced long-lasting ecosystem changes on a semi-arid tropical island—the case of Boka Bartol (Bonaire, Leeward Antilles) - Max Engel; Helmut Brückner; Sascha Fürstenberg; Peter Frenzel; Anna Maria Konopczak; Anja Scheffers; Dieter Kelletat; Simon Matthias May; Frank Schäbitz; Gerhard Daut (The Science of Nature, 2013)

Towards bioremediation of toxic unresolved complex mixtures of hydrocarbons: identification of bacteria capable of rapid degradation of alkyltetralins - Max Frenzel; Philip James; Sara K. Burton; Steven J. Rowland; Hilary M. Lappin-Scott (Journal of Soils and Sediments, 2009)